2019
DOI: 10.12998/wjcc.v7.i20.3185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of robotic vs laparoscopic radical hysterectomy for cervical cancer

Abstract: BACKGROUNDCervical cancer is the most common gynecological malignancy, ranking first in female reproductive malignancies with more than 500000 new cases and 275000 deaths each year. Traditionally, open radical hysterectomy is considered the standard surgical procedure for the treatment of resectable cervical cancer. The latest guidelines from the National Comprehensive Cancer Network and the European Society of Gynecological Oncology suggest that open surgery and laparoscopic surgery (using traditional laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…The MIS arm of this trial consisted predominately of conventional laparoscopy with only 15.6% of the patients undergoing robot‐assisted surgery. Multiple subsequent observational studies have substantiated these results regarding MIS, 10–13 whereas others reported non‐inferiority of recurrence and survival rates after (specifically) robot‐assisted surgery 14–16 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The MIS arm of this trial consisted predominately of conventional laparoscopy with only 15.6% of the patients undergoing robot‐assisted surgery. Multiple subsequent observational studies have substantiated these results regarding MIS, 10–13 whereas others reported non‐inferiority of recurrence and survival rates after (specifically) robot‐assisted surgery 14–16 …”
Section: Introductionmentioning
confidence: 96%
“…Multiple subsequent observational studies have substantiated these results regarding MIS, [10][11][12][13] whereas others reported non-inferiority of recurrence and survival rates after (specifically) robotassisted surgery. [14][15][16] A large population-based cohort study in Sweden, where cervical cancer surgery is highly centralised, recently concluded it to be safe to continue with robot-assisted surgery when performed by experienced, high-volume surgeons. 14 In the previous studies, the learning-curve effect on oncological outcomes in cervical cancerspecifically in robotassisted laparoscopyis not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Barrie et al and Chen et al both found no significant differences in intraoperative complications but showed substantial reductions in postoperative complications for the RH patients [15,19]. Early postoperative complications were mainly wound and urinary tract infections, while long-term postoperative complications included lymphatic drainage disorders [19]. Meanwhile, Ngan et al suggest that some postoperative complications, such as respiratory failure, are higher in RH patients due to higher risks of facial and upper-airway edema resulting from longer OT in the steep Trendelenburg position [32].…”
Section: Overall Complication Ratementioning
confidence: 93%
“…Fifteen reviewed studies measured the complication rates in RH and CLH: of these, 11 studies found no statistical difference between the approaches and one study showed a higher complication rate in CLH; additionally, three studies found differences after complication classification. Barrie et al and Chen et al both found no significant differences in intraoperative complications but showed substantial reductions in postoperative complications for the RH patients [15,19]. Early postoperative complications were mainly wound and urinary tract infections, while long-term postoperative complications included lymphatic drainage disorders [19].…”
Section: Overall Complication Ratementioning
confidence: 94%
See 1 more Smart Citation